A cultural look at moral purity: wiping the face clean - Lee, Spike W. S.; Tang, Honghong; Wan, Jing; Mai, Xiaoqin; Liu, Chao (Frontiers in Psychology, 2015)
Morality is associated with bodily purity in the custom of many societies. Does that imply moral purity is a universal psychological phenomenon? Empirically, it has never been examined, as all prior experimental data came from Western samples. Theoretically, we suggest the answer is not so straightforward—it depends on the kind of universality under consideration. Combining perspectives from cultural psychology and embodiment, we predict a culture-specific form of moral purification. Specifically, given East Asians’ emphasis on the face as a representation of public self-image, we hypothesize that facial purification should have particularly potent moral effects in a face culture. Data show that face-cleaning (but not hands-cleaning) reduces guilt and regret most effectively against a salient East Asian cultural background. It frees East Asians from guilt-driven prosocial behavior. In the wake of their immorality, they find a face-cleaning product especially appealing and spontaneously choose to wipe their face clean. These patterns highlight both culturally variable and universal aspects of moral purification. They further suggest an organizing principle that informs the vigorous debate between embodied and amodal perspectives.